Aberrant Lymphatic Drainage of Primary Invasive Lobular Carcinoma with Concurrent Primary Lung Adenocarcinoma: A Case Report - Lee, Rina Won; Denney, Emily (International Journal of Medical Students, 2020)
Background: Lymphatic spread of breast cancer is currently well understood and can be assessed in breast cancer patients through the use of lymphatic mapping with sentinel node biopsy, CT, PET. The Case: Here we present a case report of a 73-year-old female with two distinct primary carcinomas, right-sided invasive lobular carcinoma of the breast and left-sided adenocarcinoma of the lung. We also discuss the predictable and unpredictable lymphatic drainage of the lobular carcinoma, including ipsilateral drainage to the axillary chain and suspected contralateral hilar and mediastinal lymph node metastasis. Conclusion: The unique lymphatic spread of breast cancer, in this case, emphasizes the use of lymphatic mapping for the staging of disease and staining biopsied tissue samples for tumor markers to guide treatment. Additional anatomic research in this patient or supporting reported cases are needed to determine the frequency and cause of aberrant lymphatic drainage of primary invasive lobular carcinoma of the breast.